The Family and Community Nurse Core Competencies: integrating European standards into the Italian context - Camedda, Claudia; Scalorbi, Sandra; Longobucco, Yari (Acta Biomedica Atenei Parmensis, 2021)
The SARS-Cov-2 pandemic has restored the attention of policy-makers on the essentiality of Primary Care and the need of the Family and Community Nurses (FCNs), in order to ensure the proactive interception of individuals, families and community needs. In Italy, the Decree-Law no.34 of 19 May 2020 was issued, officially introducing the FCN. Therafter, it has been elaborated the "Address lines of the FCN proposal", starting from the “Position Statement on Family and Community Nurses" of the Italian National Federation of Nursing Professions Orders. In Europe, the ENhANCE (EuropeaN-curriculum-for-fAmily-aNd-Community-nursE) project has defined a standardized professional profile of the FCNs, based on specific Core Competencies. The aim of this work was to investigate and integrate the differences between the two profiles. In order to carry out this comparison, these competencies were compared and integrated with those identified by the Tuning model (TM), which identifies the knowledge, the skills and the attitudes that all newly graduated nurses must have acquired at the end of their education programme. Nine of the eleven italian competencies are included among the twenty-eight competencies of ENhANCE. The same applies to two of three competencies identified in the TM. As a result, this benchmark has resulted in a list of 30 competencies. This benchmark integrates the european profile with the national one, also oriented to their effective applicability in educational setting thanks to the TM. Through this comparison it is possible to develop professional educational projects, in order to standardize the grounding process on the national context.